Birth, distress and disease: Placental-brain interactions - Power, Michael L (Cambridge University, 2013)
This volume examines the role of steroids and peptides in the regulation of pregnancy and pregnancy outcome, and their long-term effects including possible influences on adult-onset diseases. Perturbations to this regulatory system can result in poor pregnancy outcome. This is a fascinating account of an important area of materno-fetal medicine.